2011
DOI: 10.1371/journal.pone.0023526
|View full text |Cite
|
Sign up to set email alerts
|

Radiolaria Divided into Polycystina and Spasmaria in Combined 18S and 28S rDNA Phylogeny

Abstract: Radiolarians are marine planktonic protists that belong to the eukaryote supergroup Rhizaria together with Foraminifera and Cercozoa. Radiolaria has traditionally been divided into four main groups based on morphological characters; i.e. Polycystina, Acantharia, Nassellaria and Phaeodaria. But recent 18S rDNA phylogenies have shown that Phaeodaria belongs within Cerocozoa, and that the previously heliozoan group Taxopodida should be included in Radiolaria. 18S rDNA phylogenies have not yet resolved the sister … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…The Rhizaria tree (Fig. 3B) showed the grouping of Chlorarachniophyta and Monadofilosa (from the phylum Cercozoa), while Radiolaria was not well defined as described in previous phylogenies [23]: the class Polycystinea did not appear monophyletic and was separated into the respective orders except Collodaria and Nassellaria that were grouped (as Nassellaria*). These trees confirmed that the final dataset did not contain misclassified sequences.…”
Section: Resultsmentioning
confidence: 72%
“…The Rhizaria tree (Fig. 3B) showed the grouping of Chlorarachniophyta and Monadofilosa (from the phylum Cercozoa), while Radiolaria was not well defined as described in previous phylogenies [23]: the class Polycystinea did not appear monophyletic and was separated into the respective orders except Collodaria and Nassellaria that were grouped (as Nassellaria*). These trees confirmed that the final dataset did not contain misclassified sequences.…”
Section: Resultsmentioning
confidence: 72%
“…Taxopodida and Acantharia have been grouped together as Spasmaria based on the existence of contractile myonemes in both groups (Cavalier-Smith 1993), a grouping also supported in combined 18S and 28S rDNA phylogeny (Krabberød et al 2011). Myonemes give taxopodidans the ability to swim using their pseudopodia like oars, while giving acantharians the ability to regulate their buoyancy by altering their cell volume (Cachon et al 1977; Febvre 1981).…”
Section: Discussionmentioning
confidence: 96%
“…; Krabberød et al. ), the sequence data need to be sampled from both subgroups to accurately elucidate the evolution of EF‐1α/EFL gene in Radiolaria, as well as that in Rhizaria as a whole.…”
mentioning
confidence: 99%